Living hell - Yarsky, Caitlin (Dark Horse Books, 2025)
"Meet Jerome Jameel - a loving father and husband who also happens to be a demon. He's fled his former prison of Hell to live incognito on earth as a bartender, hiding in plain sight. Jerome is determined to stay out of trouble, but when he kills one of Hell's most vicious bounty hunters in self-defense, he inherits the job of infernal bailiff, hunting down his own kind. Jerome soon faces a range of ancient deities and monsters, from the human-eating ghosts known as Jikininki to psychopomps like Baron Samedi. But with every act of betrayal, Jerome loses a little more of his hard-earned humanity"--